Edge stress intensity functions along elliptic and part-elliptic 3D cracks. (15th March 2021) - Yosibash, Zohar; Schapira, Yaron
Abstract: Three-dimensional part-elliptic crack fronts are common in engineering practice. Herein we formulate a computational method, known as the quasidual function method (QDFM) for the functional representation of edge stress intensity functions (ESIFs) along such cracks in 3D domains. It is an efficient post-processing algorithm that may use the finite element solution away from the singular edge. Numerical examples including an internal elliptic crack, a surface half-elliptic crack and a quarter elliptic crack from a hole are provided, demonstrating the efficiency and accuracy of the proposed method. Highlights: The QDFM was formulated for extracting edge stress intensity function along elliptic and part-elliptic cracks. Very accurate ESIFs are extracted from finite element (FE) solutions without the need of a refined FE mesh. Numerical examples of a semi-elliptic surface crack and part-elliptic crack at holes are provided.